Perkembangan Kemampuan Anak Masa Usia Berumur 7 Tahun - Ramadhan Lubis; Tania Salsabila; Badrun Nafiza; Saqilah Romatua Hasibuan; M. Hafiz Alfiandi; Fatimah Zahara Karniawan (FKIP, Universitas Palangka Raya, 2026)
This study aims to analyze the development of children's abilities aged 7 years. The focus of the study discussed in this research is the characteristics of child development, factors that influence child development and educational implications for children aged 7 years. The research method used is qualitative based on descriptive studies. The data collection techniques used were observation, interviews and documentation studies. The data obtained was then analyzed using the Miles and Huberman technique, namely data reduction, data display, and drawing conclusions. The results of the research explain that at this time all children's potential needs to be encouraged so that they will develop optimally. In line with the results of interviews with children aged 7 years above, namely that they can read, write and count, children often experience problems with their own moods, they still like to sulk or their thinking patterns are not yet very mature. The ability to speak has started to become fluent, able to communicate with those around him, starting to have the courage to speak. Factors that influence a child's development can be physical, the surrounding environment, a person's personality and so on. Meanwhile, the implications of education for the development of abilities of 7 year old children generally affect the child's cognitive, moral and psychomotor aspects. This is why the role of teachers and parents is important in the development of 7 year old children in the realm of education.